(untitled) (Research, Society and Development, 2019)
Due to the various social changes that have occurred to meet voluntary demands, there is the emergence of organic volunteering. This type of volunteering refers to volunteering that acts when the actions aim to meet specific demands of the communities (SELLI, GARRAFA, 2005). Engineers Without Borders is a worldwide ONG with representation in Brazil, with 64 nuclei (ESF, 2018), among them, the nucleus of Joao Monlevade. The ESF proposes the alignment of engineering to the service of the community, becoming an important tool for the development of interpersonal relations and for the community contribution with projects shaped to the specific social needs. The objective of this study is to highlight the voluntary organization, through the organization Engineers Without Borders, as one of the pathways of personal development and humanized training of engineering students. In this way, through the execution of social projects, the students have the possibility to visualize the demands of the local communities, bringing them closer to the realities not lived in classrooms. The methodology consists of an action research in order to expose the projects carried out by members of Engineers Without Borders Joao Monlevade and demonstrate the impact of this nucleus on the lives of students and the community involved. In this initial cycle, the nucleus of Joao Monlevade took place with 30 direct members, coming from the State University of Minas Gerais, Joao Monlevade Unit. In 2018, three projects were carried out at the Crê-Ser Foundation, in Joao Monlevade, Minas Gerais: Bioeduca, the Kitchen Reform and the Agroecological Vegetable Garden. The projects provided interaction and sharing of knowledge to the participants, as well as the practice of sustainability, improvement of food quality and knowledge applied to the students involved. The results obtained from the creation of the group reaffirm the relevance of the university extension in the training of students, in the development of critical thinking, in the risk analysis of the projects and in the strengthening of the ethics of the members involved.